Mandatory disclosure and corporate green innovation - Bratten, Brian; Cheng, Sung-Yuan Mark; Kleppe, Tyler J. (Review of Accounting Studies, 2026)
We examine the relation between mandatory environmental disclosure and corporate green innovation. Adopting a difference-in-differences research design, we find that the adoption of state-level greenhouse gas emissions disclosure mandates is associated with an increase in the quantity of patents related to climate change mitigation/adaptation technologies (i.e., “green innovations”). This increase is stronger among firms with more environmental investors, suggesting investor preferences influence this relation. We also document a positive association between these mandates and firms’ future environmental performance ratings, suggesting a positive externality. However, we find that these mandates are associated with a reduction in future financial performance for some firms, suggesting a potential negative effect on shareholder welfare. Collectively, our results provide new evidence on the real effects of mandatory environmental disclosure and the determinants of green innovation and contribute to the literature on the motivations for green innovation and the literature on corporate disclosure and investment decisions.